QUANTUM COMPUTING: A TECHNICAL DEEP DIVE INTO THE NEXT COMPUTING FRONTIER - Vinay Kumar Ankusarao, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Quantum computing represents a revolutionary paradigm in computational technology, promising to transform this article's approach to solving complex problems across various domains. This comprehensive article explores the fundamental principles, recent breakthroughs, and future prospects of quantum computing technology. The article examines the core concepts of quantum bits and superposition, along with advances in quantum parallelism and entanglement. Special attention is given to Google's Willow quantum chip and its implications for error correction and quantum state preservation. The article covers the integration of quantum computing with artificial intelligence, highlighting improvements in machine learning capabilities and computational efficiency. The article also addresses current technical challenges in maintaining quantum coherence at scale and developing robust error correction systems, while outlining promising research directions in quantum architecture design and algorithm development.